2021
DOI: 10.1101/2021.11.14.468538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstruction of sound driven, actively amplified and spontaneous motions within the tree cricket auditory organ

Abstract: Hearing consists of a delicate chain of events. Sound is first captured by an eardrum or similar organ which is set into vibrations, these vibrations must then be transmitted to sensory cells in a manner that opens mechanosensory channels generating an electrical signal. Studying this process is challenging. Auditory vibrations are in the nano- to picometer-scale and occur at fast temporal scales of milli to microseconds. Finally, most of this process occurs within the body of the animal where it is inaccessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 64 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…However, in 2021, the bushcricket (Tettigoniidae) ‘tracheal septum’, a structure that is analogous to the field cricket dividing membrane, was shown by optical coherence tomography (OCT) to move in-phase with the PTM, thus indicating its role in mechanically coupling transmission from the PTM to the sensory neurons [47]. In the same year, an OCT study on the tree cricket (Oecanthinae) acoustic trachea revealed similar results [24]. While the morphology of the field cricket tracheal branches differs from that of these ensiferans, our findings align with these recent studies and reinforce the importance of continuing to investigate how tracheal structures mechanically transmit and filter signals from the tympana to the auditory neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in 2021, the bushcricket (Tettigoniidae) ‘tracheal septum’, a structure that is analogous to the field cricket dividing membrane, was shown by optical coherence tomography (OCT) to move in-phase with the PTM, thus indicating its role in mechanically coupling transmission from the PTM to the sensory neurons [47]. In the same year, an OCT study on the tree cricket (Oecanthinae) acoustic trachea revealed similar results [24]. While the morphology of the field cricket tracheal branches differs from that of these ensiferans, our findings align with these recent studies and reinforce the importance of continuing to investigate how tracheal structures mechanically transmit and filter signals from the tympana to the auditory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The tracheal branches of the ensiferan ear have previously been thought to function mainly to channel sound in the air column to the tympana [ 24 ]. However, in 2021, the bushcricket (Tettigoniidae) ‘tracheal septum’, a structure that is analogous to the field cricket dividing membrane, was shown by optical coherence tomography (OCT) to move in-phase with the PTM, thus indicating its role in mechanically coupling transmission from the PTM to the sensory neurons [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two modalities may therefore simply aid in the tonotopy of the CA, which then begins to further filter vibrations by their frequency composition. Non-invasive mechanical measurements of the CA of C. monstrosa by novel methods such as optical coherence tomography [ 18 , 46 ] would be useful in clarifying the relative contribution of the tympana to overall frequency discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown in Tettigoniidae that the DW of the anterior tracheal branch is tonotopic and contributes heavily to the mechanotransduction process [ 18 ]. Given that the anterior tympanum and mechanosensory units of C. monstrosa are mechanically coupled by the anterior tracheal branch like in most Ensiferans [ 46 ], we postulate that the tonotopic vibrations of the DW have originated from a tonotopic tympanum, with the vibrations shifting dorsally along the anterior tracheal branch over evolutionary time to reduce internal attenuation of the peripheral mechanical displacement. Observations of the displacement of the tympana of tettigoniid species show that while the CA and DW are tonotopic, the tympana are not [ 10 , 11 , 35 ], and thus the tonotopic arrangement may have simply shifted to the DW, with the process of hearing involving an additional mechanical step [ 8 , 18 , 35 ].…”
Section: Discussionmentioning
confidence: 99%